Periclase-spinel refractory material and preparation method thereof

Prepare magnesium-spinel refractory materials by electromelting, add titanium oxide and zirconium oxide to form magnesium titanate and zirconium titanate phases, which solves the problem of magnesium chromium bricks being susceptible to slag penetration and smelting cast magnesium chromium refractory materials being easily cracked The problem is to improve the high-temperature thermal shock resistance and hydration resistance of the material.

CN119390429APending Publication Date: 2025-02-07RUITAI MATERIALS TECHNOLOGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411785798.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing magnesium-chromium bricks are susceptible to penetration and erosion by slag during smelting, and molten cast magnesium-chromium refractory materials are prone to cracking at high temperatures, which affects their service life and safety.

Method used

The magnesium-spinel refractory material is prepared by electrofusion. By adding titanium oxide and zirconium oxide, Ti4+ is used to replace the Mg2+ position in the MgO lattice, forming lattice distortion and magnesium titanate phase, absorbing free CaO, and improving heat resistance The seismic performance and the reaction of ZrO2 with TiO2 forms a zirconium titanate phase, which promotes the generation of intergranular cracks to relieve thermal stress.

Benefits of technology

It improves the thermal shock resistance and hydration resistance of refractory materials, reduces the risk of slag penetration, and extends the service life of the materials. It is suitable for high-temperature environments such as copper smelting industrial furnaces and glass kilns.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a periclase-spinel refractory material and a preparation method thereof, the periclase-spinel refractory material comprises the following raw materials: 60-75% of magnesia, 5-18% of magnesium aluminate spinel, 5-17% of magnesium-chromium sand, 3-9% of titanium oxide and 2-6% of zirconium oxide, the titanium oxide and the zirconium oxide which are ball-milled and premixed are mixed with other raw materials, the mixture is melted at 2000-2200 DEG C, cast, annealed at the temperature of less than or equal to 0.1 DEG C / kg.h and subjected to heat preservation, and then cut, ground and processed into a finished product. The periclase-spinel refractory material disclosed by the invention is low in porosity, high in strength, good in alkaline slag corrosion resistance and excellent in thermal shock resistance, and is stable in performance and long in service life when being used for industrial kiln linings for nonferrous metallurgy, glass, cement and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a periclase-spinel refractory material and a preparation method thereof, and belongs to the field of refractory materials of inorganic non-metallic material discipline. Background Art

[0002] Sintered magnesia-chrome bricks are commonly used refractory materials in key parts of non-ferrous smelting furnaces. However, with the influx of domestic waste non-ferrous metal raw materials into the market, the amount of slag generated during the smelting process has increased significantly and the wettability and permeability of the slag have increased, resulting in high consumption and low life of magnesia-chrome bricks, affecting the safe operation of the kiln. In response to the problem of slag penetration, a common method is to reduce the porosity of magnesia-chrome bricks. Patent CN107298587B discloses a low-porosity magnesia-chrome brick used in the non-ferrous industry and its production method. Although the invention has a porosity of less than 12% and has good corrosion resistance, there are still many pores around the crystals produced after the magnesia-chrome bricks are impregnated and dried, and the crystal corrosion resistance is worse than that of chrome 20 sand, and there is still a risk of slag penetration. Patent CN106588050B discloses a low-porosity magnesia-chrome brick for nonferrous smelting and a preparation method thereof. The invention adopts a process of nano-alumina suspension impregnation and microwave treatment. Although it effectively reduces the porosity of the magnesia-chrome brick and refines the pore diameter, it is limited by the pressing and sintering processes. There are still many tiny pores that absorb and buffer thermal stress, which are easily penetrated and eroded by slag.

[0003] Due to its own dense characteristics, the slag can only be dissolved on its surface but cannot penetrate, showing excellent resistance to erosion and penetration of non-ferrous smelting slag. Patent CN102241520B discloses a method for melting and casting α-alumina products. Although the invented material has no cracks, dense structure, high refractoriness and high-temperature structural strength, and good high-temperature chemical stability, the use of a large amount of waste non-ferrous metal raw materials leads to a more complex composition of the slag. The presence of components such as SiO2 and FeO in the slag may increase the solubility of α-Al2O3 in the slag and promote the destruction of the product structure.

[0004] Chromium oxide has excellent corrosion resistance to molten melt and slag. Patent CN114507077B discloses a fused-cast zirconium-chromium-corundum refractory brick and its preparation method. Although the material has high density and good alkali corrosion resistance, the price of chromium oxide and zirconium oxide is expensive and the melting point is high. The large-scale introduction of chromium oxide and zirconium oxide has the problem of high material production cost. Shi Jie et al. found that fused-cast magnesia-chrome bricks have better resistance to corrosion and penetration of non-ferrous smelting slag than sintered magnesia-chrome bricks, but fused-cast magnesia-chrome refractory materials have the problem of easy stress concentration at high temperatures and are prone to cracking.

[0005] In order to solve the problem that the fused-cast magnesium-chromium refractory is easy to crack, the present invention adds titanium oxide and zirconium oxide and adopts electric melting to prepare periclase-spinel refractory, and utilizes the low eutectic characteristics of magnesia sand and titanium oxide to reduce the melting temperature of magnesia sand. 4+ Substitute Mg in MgO lattice 2+ Position, forming lattice distortion, and generating cation vacancies, which play a binding role on the surrounding atoms, forming intergranular magnesium titanate phase between the condensed and crystallized periclase, magnesium aluminum spinel and magnesium chromium spinel phases, and using the difference in thermal expansion coefficients between the zirconium titanate phase and the magnesium titanate phase formed by the reaction of ZrO2 and TiO2 to promote the generation of intergranular cracks to relieve thermal stress and volume effect, so that the refractory material has good thermal shock stability. At the same time, because the periclase-spinel refractory material prepared by electric melting is not easily corroded by alkaline slag, it is also suitable for use in severely corroded parts of glass kilns and cement rotary kilns. Summary of the invention

[0006] The present invention discloses a periclase-spinel refractory material and a preparation method thereof, wherein the raw materials in the formula are as follows in terms of weight percentage: (1) 60~75% magnesia, (2) Magnesium aluminum spinel 5~18%, (3) Magnesium chrome sand 5~17%, (4) Titanium oxide 3~9%, (5) Zirconia 2~6%.

[0007] The (4) titanium oxide can be titanium dioxide, high titanium material, artificial rutile, etc., wherein the weight percentage of TiO2 is ≥99%, and the weight ratio of titanium oxide to magnesia is 0.05-0.12, and the weight ratio of titanium oxide to zirconium oxide is 1.5.

[0008] The specific process steps are as follows: Titanium oxide and zirconium oxide are premixed and ball-milled to a uniform state, added to magnesia chrome sand and magnesia aluminum spinel, and finally magnesia sand is added to form a starting batch; the batch is melted at 2000-2200°C; a three-layer structure insulation box is made, with a sand mold made of graphite plate as the innermost layer, insulation materials such as mullite lightweight bricks, clay lightweight bricks, and high-aluminum lightweight bricks as the middle insulation layer, and waste powder and iron shells produced by production as the outermost layer; the material is cast in the insulation box to ensure that the material is insulated and annealed at a cooling rate of ≤0.1°C / kg·h; the electro-melted prepared periclase-spinel refractory material after insulation and annealing is cut and ground into the desired finished product.

[0009] The reasons for the weight ratio of each component of the present invention are as follows: The eutectic temperature of TiO2 and MgO is much lower than the melting temperature of MgO. By adding titanium oxide (TiO2 weight percentage ≥ 99%), the melting temperature of periclase spinel material can be effectively reduced. If the weight percentage of titanium oxide is less than 99%, the introduction of impurities will lead to the formation of more glass phase in the material, affecting the corrosion resistance of the material.

[0010] The weight ratio of titanium oxide to magnesia is preferably 0.05-0.12. TiO2 in titanium oxide reacts with MgO in magnesia to form magnesium titanate phase between the periclase phase and the spinel phase. At the same time, TiO2 absorbs free CaO in magnesia to form calcium titanate phase, which improves the material's hydration resistance and thermal shock resistance. If the weight ratio is less than 0.05, the magnesium titanate phase formed in the material is difficult to be evenly dispersed between the periclase phase, magnesium aluminum spinel, and magnesium chromium spinel, which has a negative impact on the material's thermal shock resistance; if the weight ratio is greater than 0.12, it causes the rich aggregation of calcium titanate phase, which is not conducive to the densification of the material.

[0011] The weight ratio of titanium oxide and zirconium oxide should be 1.2~2. The main reason is that when the weight ratio of ZrO2 and TiO2 is 1.2~2, it is easy to form a stable zirconium titanate phase, which synergistically improves the thermal shock resistance of the material with the magnesium titanate phase; if the weight ratio is <1.2 or >2, it is easy to form a metastable zirconium titanate phase, which is easy to decompose during the cooling annealing process.

[0012] Compared with the prior art, the technical characteristics of the electric melting method for preparing periclase-spinel refractory materials in the present invention are as follows: Taking advantage of the low melting temperature of TiO2, MgO and ZrO2 in titanium oxide, the melting temperature of periclase spinel prepared by electric melting is reduced. 4+ Substitute Mg in MgO lattice 2+ Position, forming an intergranular magnesium titanate phase between the periclase phase and the spinel phase, and absorbing free CaO, thereby improving the thermal shock resistance and hydration resistance of the material.

[0013] By utilizing the difference in thermal expansion coefficients between the zirconium titanate phase and the magnesium titanate phase formed by the eutectic of ZrO2 and TiO2, the generation of intergranular cracks is promoted. This can improve the material's thermal shock resistance while ensuring its resistance to slag penetration, thereby extending the material's service life in copper smelting industrial furnaces and all-oxygen combustion glass kilns. DETAILED DESCRIPTION

[0014] Example 1

[0015] According to the following formula (weight and particle size content): (1) Magnesium oxide 75%, (2) Spinel 5%, (3) Magnesium chrome sand 5%, (4) Titanium oxide (TiO2 weight percentage 99.1%) 9%, (5) Zirconium oxide 6%.

[0016] The specific process steps include the following parts: premixing titanium oxide and zirconium oxide and ball-milling them to a uniform state, adding them to magnesia chrome sand and magnesia aluminum spinel, and finally adding magnesia sand to form a starting batch; melting the batch at 2000°C; making a three-layer structure insulation box of graphite sand mold, mullite lightweight brick, waste powder and iron shell; casting the material in the insulation box, keeping it warm at a cooling rate of 0.1°C / kg·h, and annealing; cutting and grinding the electro-melted prepared periclase-spinel refractory material after keeping warm and annealing into the required finished product. Example 2

[0017] According to the following formula (weight and particle size content): (1) Magnesium oxide 67%, (2) Spinel 12%, (3) Magnesium chrome sand 11%, (4) Titanium oxide (TiO2 weight percentage 99.5%) 6%, (5) Zirconium oxide 4%.

[0018] The specific process steps include the following parts: premixing titanium oxide and zirconium oxide and ball-milling them to a uniform state, adding them to magnesia chrome sand and magnesia aluminum spinel, and finally adding magnesia sand to form a starting batch; melting the batch at 2100°C; making a three-layer structure insulation box of graphite sand mold, clay lightweight brick, waste powder and iron shell; casting the material in the insulation box, keeping it warm at a cooling rate of 0.09°C / kg·h, and annealing; cutting and grinding the electro-melted prepared periclase-spinel refractory material after keeping warm and annealing into the required finished product. Example 3

[0019] According to the following formula (weight and particle size content): (1) 60% magnesia, (2) Spinel 18%, (3) Magnesium chrome sand 17%, (4) Titanium oxide (TiO2 weight percentage 99.8%) 3%, (5) Zirconium oxide 2%.

[0020] The specific process steps include the following parts: premixing titanium oxide and zirconium oxide and ball-milling them to a uniform state, adding them to magnesia-chrome sand and magnesia-alumina spinel and mixing them, and finally adding magnesia sand to form a starting batch; melting the batch at 2200°C; making a three-layer structure insulation box of graphite sand molds, high-alumina lightweight bricks, waste powder and iron shell; casting the material in the insulation box, keeping it warm at a cooling rate of 0.1°C / kg·h, and annealing; cutting and grinding the electro-melted prepared periclase-spinel refractory material after keeping warm and annealing into the required finished product. Comparative Example 1

[0021] According to the following formula (weight and particle size content): (1) Magnesium oxide 75%, (2) Spinel 11%, (3) Magnesium chrome sand 9%, (4) Titanium oxide (TiO2 weight percentage 99%) 3%, (5) Zirconium oxide 2%.

[0022] The specific process steps include the following parts: premixing titanium oxide and zirconium oxide and ball-milling them to a uniform state, adding them to magnesia chrome sand and magnesia aluminum spinel, and finally adding magnesia sand to form a starting batch; melting the batch at 2000°C; making a three-layer structure insulation box of graphite sand mold, mullite lightweight brick, waste powder and iron shell; casting the material in the insulation box, keeping it warm at a cooling rate of 0.1°C / kg·h, and annealing; cutting and grinding the electro-melted prepared periclase-spinel refractory material after keeping warm and annealing into the required finished product.

[0023] Table 1 lists the properties of Comparative Example 1. Compared with Example 1, the preparation process is the same, but the weight ratio of titanium oxide to magnesia is 0.04. After 9 water-cooling thermal shock tests, the material has obvious cracks. Therefore, it is necessary to have a weight ratio of titanium oxide to magnesia of ≥ 0.05. Comparative Example 2

[0024] According to the following formula (weight and particle size content): (1) Magnesium oxide 70%, (2) Spinel 10%, (3) Magnesium chrome sand 9%, (4) Titanium oxide (TiO2 weight percentage 99.8%) 9%, (5) Zirconium oxide 2%.

[0025] The specific process steps include the following parts: premixing titanium oxide and zirconium oxide and ball-milling them to a uniform state, adding them to magnesia-chrome sand and magnesia-alumina spinel and mixing them, and finally adding magnesia sand to form a starting batch; melting the batch at 2200°C; making a three-layer structure insulation box of graphite sand molds, high-alumina lightweight bricks, waste powder and iron shell; casting the material in the insulation box, keeping it warm at a cooling rate of 0.1°C / kg·h, and annealing; cutting and grinding the electro-melted prepared periclase-spinel refractory material after keeping warm and annealing into the required finished product.

[0026] Table 1 lists the properties of Comparative Example 2. Compared with Example 3, the preparation process is the same, but the weight ratio of titanium oxide to magnesia is 0.13, the densification degree of the sample is reduced, and the corrosion resistance of the material is reduced. Therefore, "the weight ratio of titanium oxide to magnesia is 0.05-0.12" is necessary. Comparative Example 3

[0027] According to the following formula (weight and particle size content): (1) Magnesium oxide 71%, (2) Spinel 5%, (3) Magnesium chrome sand 5%, (4) Titanium oxide (TiO2 weight percentage 99%) 10%, (5) Zirconium oxide 9%.

[0028] The specific process steps include the following parts: premixing titanium oxide and zirconium oxide and ball-milling them to a uniform state, adding them to magnesia chrome sand and magnesia aluminum spinel, and finally adding magnesia sand to form a starting batch; melting the batch at 2000°C; making a three-layer structure insulation box of graphite sand mold, mullite lightweight brick, waste powder and iron shell; casting the material in the insulation box, keeping it warm at a cooling rate of 0.1°C / kg·h, and annealing; cutting and grinding the electro-melted prepared periclase-spinel refractory material after keeping warm and annealing into the required finished product.

[0029] Table 1 lists the properties of Comparative Example 3. Compared with Example 1, the preparation process is the same, but the weight ratio of titanium oxide to zirconium oxide is 1.1, and the apparent porosity of the material is significantly improved. The main reason is that the decomposition of metastable zirconium titanate leads to an increase in porosity and a decrease in the resistance to slag penetration. Therefore, it is necessary to have a weight ratio of titanium oxide to zirconium oxide ≥ 1.2. Comparative Example 4

[0030] According to the following formula (weight and particle size content): (1) Magnesium oxide 67%, (2) Spinel 12%, (3) Magnesium chrome sand 12.2%, (4) Titanium oxide (TiO2 weight percentage 99.5%) 6%, (5) Zirconia 2.8%.

[0031] The specific process steps include the following parts: premixing titanium oxide and zirconium oxide and ball-milling them to a uniform state, adding them to magnesia chrome sand and magnesia aluminum spinel, and finally adding magnesia sand to form a starting batch; melting the batch at 2100°C; making a three-layer structure insulation box of graphite sand mold, clay lightweight brick, waste powder and iron shell; casting the material in the insulation box, keeping it warm at a cooling rate of 0.09°C / kg·h, and annealing; cutting and grinding the electro-melted prepared periclase-spinel refractory material after keeping warm and annealing into the required finished product.

[0032] Table 1 lists the properties of Comparative Example 4. Compared with Example 2, the preparation process is the same, but the weight ratio of titanium oxide to zirconium oxide is 2.1, and the apparent porosity of the material is significantly improved. The main reason is that the decomposition of metastable zirconium titanate leads to an increase in porosity and a decrease in the resistance to slag penetration. Therefore, it is necessary to have a weight ratio of titanium oxide to zirconium oxide of 1.2 to 2. Comparative Example 5

[0033] According to the following formula (weight and particle size content): (1) Magnesium oxide 75%, (2) Spinel 5%, (3) Magnesium chrome sand 5%, (4) Titanium oxide (TiO2 weight percentage 99%) 9%, (5) Zirconium oxide 6%.

[0034] The specific process steps include the following parts: adding the raw materials into a mixer according to proportion, adding lignin or phosphate binder and mixing evenly; pressing and forming with a 1000t press; drying naturally for 36 hours, and then drying at 260°C for 48 hours; loading the dried semi-finished product into a tunnel kiln and keeping it at 1800°C for 9 hours; cutting and grinding the sintered periclase-spinel refractory material into the required finished product.

[0035] Table 1 lists the performance of comparative example 5. Compared with Example 1, the raw material formula is the same, and the sintering process is adopted. Due to the huge difference in thermal expansion coefficients between magnesia-alumina spinel, magnesia-chrome sand and periclase, the generated magnesium titanate phase is not dispersed between the crystals, the hoop tensile stress causes an increase in large cracks in the material, and the material performance is significantly worse than that of the fused material.

[0036] The performance comparison of the materials prepared in the above examples and the comparative examples is shown in Table 1: Table 1 Comparison of refractory properties index Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 <![CDATA[Bulk density g / cm 3 > 3.58 3.63 3.64 3.52 3.61 3.57 3.59 3.02 Apparent porosity% 1.1 1.0 0.8 2.2 3.8 5.3 7.9 13.4 Normal temperature compressive strength MPa 287 291 297 160 257 228 235 92 Resistance to high-alkali glass melt corrosion (mm, 1200℃×24h) 0.10 0.10 0.10 0.11 0.23 0.22 0.26 1.2 Anti-corrosion and penetration capacity of copper smelting slag (mm, 1500℃×24h) 0.10 0.10 0.09 0.10 0.40 0.39 0.48 3.4 Thermal shock resistance (1100℃, water cooling) >10 >10 >10 9 >10 >10 >10 8

Claims

1. A periclase-spinel refractory material, the formula of which is as follows by weight percentage: (1) 60~75% magnesia, (2) Magnesium aluminum spinel 5~18%, (3) Magnesium chrome sand 5~17%, (4) Titanium oxide 3~9%, (5) Zirconia 2~6%; The titanium oxide is selected from any one of titanium dioxide, high titanium material, and artificial rutile, wherein the weight percentage of TiO2 is ≥99%; The weight ratio of titanium oxide to magnesia is 0.05-0.12; The weight ratio of titanium oxide to zirconium oxide was 1.

5.

2. A process for preparing the periclase-spinel refractory material according to claim 1, comprising the following process steps: (1) Premixing titanium oxide and zirconium oxide and ball-milling them to a uniform state, adding them to magnesia chrome sand and magnesia aluminum spinel, and finally adding magnesia sand to form a starting batch; (2) Melting the batch materials at 2000~2200℃; (3) Cast the material in an insulation box to ensure that the material is kept warm and annealed at a cooling rate of ≤0.1℃ / kg·h; (4) Cutting and grinding the electro-melted periclase-spinel refractory material after heat preservation and annealing into the desired finished product.

3. The process according to claim 2, characterized in that: In process (3), the insulation box is composed of three parts. The innermost layer is made of graphite plate to make sand mold, the middle insulation layer is made of mullite lightweight bricks, clay lightweight bricks, high-aluminum lightweight bricks and other insulation materials, and the outermost layer is filled with waste powder generated by production and wrapped with an iron shell.

Citation Information

Patent Citations

  • Method for melting and casting alpha alumina product

    CN102241520B

  • A low-porosity magnesia-chrome brick for non-ferrous smelting and its preparation method

    CN106588050B

  • A low-porosity magnesia-chrome brick for use in the non-ferrous metals industry and its production method

    CN107298587B

  • Fused cast zirconium-chromium corundum refractory bricks and their preparation methods

    CN114507077B